Colon Cancer Metastasis to the Right Testis: Case Report and Review of Literature - Mizuki Kasahara; Tomo Shimizu; Hiroshi Aoki; Mizuho Okawa; Fumito Yamabe; Hideyuki Kobayashi; Koichi Nagao; Koichi Nakajima; Yozo Mitsui (Case Reports in Urology)
Introduction. A metastatic testicular tumor is uncommon. We report here a case of testicular metastasis associated with recurrent colorectal cancer. Case Presentation. A 75-year-old male was presented with right scrotum pain one year after undergoing a right hemicolectomy combined with resection of the small intestine and omentum for ascending colon cancer (pT4N0M0). Magnetic resonance imaging of the pelvis showed a 7.3×5.4×4.5 cm mass consisting of a cystic solid tumor. A right inguinal orchiectomy was performed and right testicular pain improved after surgery. Pathology results showed that the tumor was a metastatic adenocarcinoma. The patient subsequently died two months later due to progression of the colon cancer. Conclusion. Although colorectal cancer metastasis to the testis is very uncommon, it should be kept in mind in clinical situations, especially for older males with a testicular mass or discomfort.